2006
DOI: 10.1016/j.chemosphere.2005.08.065
|View full text |Cite
|
Sign up to set email alerts
|

AhR-active compounds in sediments of the Haihe and Dagu Rivers, China

Abstract: Total concentrations of compounds that can cause activation of the aryl hydrocarbon receptor (AhR) in extracts of river sediments from various locations in the Haihe and Dagu Rivers, Tianjin, China were determined by use of the in vitro H4IIE-luc cell line. AhR-active compounds were isolated from sediments by Soxhlet extraction, and the crude extracts were fractionated using a Florisil column into three Fractions. The response of samples was compared to the TCDD standard and expressed as 2,3,7,8-tetrachlorodib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…The sum of IEQs from the fractions is 5.4 times less than the IEQ obtained for the refined hexane extract by the same analysis. The same phenomenon was also reported by Song et al (2006), and the authors suggest that it can be caused by antagonistic interactions among compounds and even their retention on the column during fractionation. In our study, antagonistic interactions in refined hexane extract are not likely since it revealed higher dioxin-like activity compared with the fractions.…”
Section: Soil Samples From the Petrochemical Plantsupporting
confidence: 49%
See 1 more Smart Citation
“…The sum of IEQs from the fractions is 5.4 times less than the IEQ obtained for the refined hexane extract by the same analysis. The same phenomenon was also reported by Song et al (2006), and the authors suggest that it can be caused by antagonistic interactions among compounds and even their retention on the column during fractionation. In our study, antagonistic interactions in refined hexane extract are not likely since it revealed higher dioxin-like activity compared with the fractions.…”
Section: Soil Samples From the Petrochemical Plantsupporting
confidence: 49%
“…Although different exposure times applied in the two bioassays, as well as different effect levels used for IEQ calculation, might contribute to the difference in IEQs, it should be stressed that unlike the H4IIE-luc analysis, the enzyme activity in micro-EROD analysis can be diminished due to the competitive inhibition (antagonistic effect) of compounds in the mixture (Brack et al 2000) including also, e.g., non-dioxin-like PCBs (Behnisch et al 2002). H4IIE-luc bioassay results (Table 4, Figures S3 and S4 in Online Resource ESM 2) for five fractions of sample P4 revealed that F2, probably containing PAHs, their derivatives, and a portion of the PCDD/Fs and PCBs (Song et al 2006), most significantly contributed to the IEQ. More polar compounds eluted in F3-F5 are not typical AhR agonists, which resulted in their lower induction potencies.…”
Section: Soil Samples From the Petrochemical Plantmentioning
confidence: 97%
“…The sediment extracts from the Yangtze River estuary showed higher EROD induction potential than those from Masan Bay [43], Tai Lake [44], and Yellow Sea [45]. The EROD induction potential of the sediment extracts from the Yangtze River estuary was also lower than that of the sediments from Tietê River [34], Morava River [14], Dagu Rivers, and Haihe [46]. Keiter et al [33] developed a classification system for AhR-mediated toxicity of German river systems.…”
Section: Resultsmentioning
confidence: 99%
“…However, the detected results had no significant correlation (P > 0.05) with the sewage treatment processes. In comparison with the Ah-R activities reported in sludge, or sediments and soils around Beijing city (Table 4), the TEQ levels (1390-6740 pg TCDD$g -1 , dw) of sewage sludge in Beijing were close to those of sewage sludge in Australia (1200-15300 pg TCDD$g -1 , dw) and Daguhe River sediments in Tianjin (1200-13900 pg TCDD$g -1 , dw), respectively [28,29,[38][39][40][41]. As the Ah-R activities of Wenyuhe River sediments (10-340 pg TCDD$g -1 , dw) [29], one of the urban drainages in Beijing, were much lower than those of the urban sewage sludge in Beijing, it could be supposed that dioxin-like pollutants were inclined to be accumulated in the sewage sludge and diluted by the drainage water.…”
Section: Aryl Hydrocarbon Receptor Activitymentioning
confidence: 96%
“…It was also found that the TEQ level of sewage sludge composted (S9) was much lower than that of the original sewage sludge (S8). Table 4 Comparison of Ah-R agonistic activities in sludge, or sediments (soils) around Beijing city [28,29,[38][39][40][41] sampling sites Ah-R agonistic activity (TEQ, pg TCDD$g sewage sludge (UK) [38] 20-220 sewage sludge (Australia) [39] 1200-15300 sewage sludge in Catalonia (Spain) [40] 10-30 soils from reclaimed water irrigated plots (Tunisia) [28] 26600-67900 sediments of Wenyuhe River in Beijing (China) [29] 10-340 sediments of Daguhe River (China) [41] 1200-13900 sewage sludge in Beijing (current study) 1390-6740…”
Section: Aryl Hydrocarbon Receptor Activitymentioning
confidence: 99%